SUPPRESSION OF ARTIFACTS IN THE PHASE-MODULATED ROTATING-FRAME IMAGING EXPERIMENT USING THE MAXIMUM-ENTROPY METHOD - Jones, J; Hore, P; Relf, C; Ouwerkerk, R; Styles, P (1992)
Phase-modulated rotating-frame imaging, a technique used. for the detection of localized metabolites in vivo, is usually implemented in a less than ideal manner because of the practical constraints imposed by the human or animal sample. As a consequence, the spectra obtained by Fourier transformation contain artifacts which distort or obscure the genuine spectral features. An attractive alternative is to use the maximum-entropy method to process the data, incorporating the time-domain response of the nuclear spins predicted by the Bloch equations. Here we demonstrate this approach using simulated data, data from phantoms, and data from the human liver and chest wall. We show that artifacts in the Fourier-transform spectra arising from off resonance effects, imperfect pulse angles, and truncation can be effectively avoided by maximum-entropy processing. © 1992.